The Role of Domestic and External Shocks in Poland : Results from an Agnostic Estimation Procedure - Andrle, Michal (IMF Working Papers; Working Paper, 2013)
This paper discusses interlinkages between Poland and the euro zone using a simple and agnostic econometric approach. Specifically, we estimate a trend-cycle VAR model using data for real and nominal variables, imposing powerful but uncontroversial assumptions that allow us to identify how external factors affect the evolution of business cycles in Poland in the period 1999-2012. Our results suggest that developments in the euro zone can explain about 50 percent of poland's output and interest rate business cycle variance and about 25 percent of the variance of inflation.